Chaos to fractals - Pulinchery, Prasanth; Pothyiodath, Nishanth; Murkoth, Udayanandan Kandoth (Universitas PGRI Kanjuruhan Malang, 2023)
In undergraduate classrooms, while teaching chaos and fractals, it is taught as if there is no relation between these two. By using some non linear oscillators we demonstrate that there is a connection between chaos and fractals. By plotting the phase space diagrams of four nonlinear oscillators and using box counting method of finding the fractal dimension we established the chaotic nature of the nonlinear oscillators. The awareness that all chaotic systems are good fractals will add more insights to the concept of chaotic systems.